P174 Extended arterial ultrasound revealing increased intima media thickness and relation to impaired microcirculation in systemic lupus erythematosus. (23rd March 2020) - Svensson, Christina; Jonasson, Hanna; Strömberg, Tomas; Eriksson, Per; Sjöwall, Christopher; Zachrisson, Helene
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic inflammatory disease characterized by multiple organ involvement. Atherosclerosis is the underlying cause of SLE-related cardiovascular disease. With high frequency ultrasound it is possible to differ between atherosclerosis and inflammatory findings in the vessel wall. Our hypothesis is that both macro- and microcirculation are impaired in SLE. Methods: Sixty patients (52 women, 8 men), range 23–63 years, classified with SLE according to the 2012 SLICC criteria, and 60 healthy controls (52 women, 8 men), range 23–63 years, were investigated. Intima-media thickness (IMT) was recorded with high frequency ultrasound (GE Logic E9) in common carotid arteries (CCA), common femoral arteries (CFA) and the aortic arch. Microcirculatory oxygen saturation was assessed with EPOS (Enhanced Perfusion and Oxygen Saturation) (PeriFlux 6000, Perimed, Järfälla, Sweden). The EPOS system measures red blood cell tissue fraction, speed resolved perfusion and oxygen saturation in the microcirculation of the skin. Results: IMT in common carotid artery (CCA) was 0.56±0.10 mm in SLE patients vs 0.54±0.13 mm in healthy controls (ns). IMT in common femoral artery (CFA) was 0.58±0.24 mm in SLE patients vs 0.48±0.12 mm in healthy controls (p<0.0001). IMT in the aortic arch was 1.21±0.63 mm in SLE patients vs 0.98±0.25 mm in healthy controls (p=0.002). Areas of increased IMT showed regular wall thickening of medium echogenicity indicating possible inflammatory origin. Microcirculation as measured with mean oxygen saturation peak was decreased in SLE patients versus controls, 83.7±7.8% vs 86.7±4.6% (p=0.01). Conclusion: This study indicates that an extended ultrasound protocol to detect possible inflammatory vessel wall changes and/or early atherosclerosis in SLE is of value. In addition we showed impaired microcirculatory function as measured with EPOS in SLE patients. Further validation of macro and microcirculatory lesions are warranted in larger studies.